As estratégias contra a erosão da superioridade militar dos estados unidos nos governos Obama e Trump: a terceira Offset Strategy como resposta aos desafios de A2/AD - Duarte, Marco Túlio Souto Maior (2019)
This monograph aims to explain, by exploratory and qualitative means, the phenomenon of the 3rd Offset Strategy. This strategy would be representative of the United States' efforts to address or overcome the strategic challenges of the post-2001 period, such as the proliferation of sensitive technologies and the emergence of highlevel strategic competitors. The present research’s object is of great importance both to the study of the United States military policy and to the Strategic Studies as a whole, considering its high potential of change in the formulation of military policies. The 3rd Offset Strategy emerges in a context of global uncertainty in which the United States military primacy is threatened by a possible loss of lead caused by issues such as economic constraints, a new technological landscape and the development of A2 / AD capabilities by its rivals. The present research aims to explain, based on a qualitative case study analysis how the United States sought to maintain its military superiority against such paradigms. For this, the monograph bases itself on the theory about the emergence of near-peer states and the modern debates about A2 / AD, represented by authors like Altman (2016), Wemyss (2016) and Sukhankin (2017) and present in United States’ official documents, such as the National Security Strategy (2017a). In order to achieve the proposed objectives, we observe and analyze the official US strategy documents in light of the academic and political debate on the subject. In conclusion, this monograph notes that the 3rd Offset Strategy is manifested in existing and ongoing policies, even after the end of the Obama administration (2009-2017) until Trump administration (2017-present), and presenting, from the budget proposal for fiscal year 2017, concrete investments that can be directly related to the proposals of the Offset Strategy